Influence of plasma parameters on the properties of ultrathin Al2O3 films prepared by plasma enhanced atomic layer deposition below 100 °C for moisture barrier applications. (25th October 2018) - Zhu, Zhen; Sippola, Perttu; Lipsanen, Harri; Savin, Hele; Merdes, Saoussen
Abstract: We report the effect of plasma parameters on the properties of ultrathin Al2 O3 films prepared by plasma enhanced atomic layer deposition for moisture barrier applications. The Al2 O3 films were grown at 90 °C using trimethylaluminum and O2 plasma as precursors. Plasma power, exposure time and O2 concentration are found to influence the growth behavior, composition and density of ultrathin Al2 O3 films. Plasma power ≥ 100 W leads to lower impurity levels and higher mass densities of ∼2.85 g·cm −3 . The optimum plasma parameters for our process, a plasma power of 100 W and an exposure time of 3 s, reveal a good water vapor transmission rate of 5 × 10 −3 g·m −2 ·day −1 for polyethylene naphthalate substrates coated with 4 nm-thick Al2 O3 films.